2008
DOI: 10.1121/1.2998780
|View full text |Cite
|
Sign up to set email alerts
|

Time-series analysis for online recognition and localization of sick pig (Sus scrofa) cough sounds

Abstract: This paper considers the online localization of sick animals in pig houses. It presents an automated online recognition and localization procedure for sick pig cough sounds. The instantaneous energy of the signal is initially used to detect and extract individual sounds from a continuous recording and their duration is used as a preclassifier. Autoregression (AR) analysis is then employed to calculate an estimate of the sound signal, and the parameters of the estimated signal are subsequently evaluated to iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…Non-invasive methods have been investigated to detect illness in several animals. For example, microphones are being used to assess coughing sounds as a warning of developing outbreak of respiratory infections [10][11][12]. Moreover, computer vision techniques have been increasingly studied to evaluate their potential to detect several illnesses in animals.…”
Section: Introductionmentioning
confidence: 99%
“…Non-invasive methods have been investigated to detect illness in several animals. For example, microphones are being used to assess coughing sounds as a warning of developing outbreak of respiratory infections [10][11][12]. Moreover, computer vision techniques have been increasingly studied to evaluate their potential to detect several illnesses in animals.…”
Section: Introductionmentioning
confidence: 99%
“…This fully automatic algorithm has been applied to the recordings of the previous subsection. Using the algorithm of Exadaktylos et al (2008b), about 50% of the manually labelled cough sounds were correctly identified by the algorithm and subsequently the result is visualised in Fig. 9, where the dark areas identify potential cough hazards.…”
Section: Fully Automatic Identification and Localisation Of Pig Coughsmentioning
confidence: 99%
“…Depending on the classification approach (e.g. Exadaktylos et al, 2008b), the characteristics of the filter can vary. However, this does not affect the performance of the sound extraction algorithm presented here.…”
Section: Extraction Of Individual Soundsmentioning
confidence: 99%
See 1 more Smart Citation
“…The strength of this technique is its non-invasiveness and the possibility to work on-line to continuously monitor the animals. The capabilities of such a system, based on the classification algorithms, have been tested in previous studies investigating respiratory diseases (Exadaktylos et al, 2008) or animal welfare . The aim is to increase our understanding of animal vocalizations and welfare by studying their responses to typical stressful conditions.…”
Section: Introductionmentioning
confidence: 99%